Magnetic temporal interference for noninvasive and focal brain stimulation. (1st February 2023) - Khalifa, Adam; Abrishami, Seyed Mahdi; Zaeimbashi, Mohsen; Tang, Alexander D; Coughlin, Brian; Rodger, Jennifer; Sun, Nian X; Cash, Sydney S
Abstract: Objective . Noninvasive focal stimulation of deep brain regions has been a major goal for neuroscience and neuromodulation in the past three decades. Transcranial magnetic stimulation (TMS), for instance, cannot target deep regions in the brain without activating the overlying tissues and has poor spatial resolution. In this manuscript, we propose a new concept that relies on the temporal interference (TI) of two high-frequency magnetic fields generated by two electromagnetic solenoids. Approach . To illustrate the concept, custom solenoids were fabricated and optimized to generate temporal interfering electric fields for rodent brain stimulation. C-Fos expression was used to track neuronal activation. Main result . C-Fos expression was not present in regions impacted by only one high-frequency magnetic field indicating ineffective recruitment of neural activity in non-target regions. In contrast, regions impacted by two fields that interfere to create a low-frequency envelope display a strong increase in c-Fos expression. Significance . Therefore, this magnetic temporal interference solenoid-based system provides a framework to perform further stimulation studies that would investigate the advantages it could bring over conventional TMS systems.